The development of electronic worksheets for students using Live worksheets and GeoGebra to enhance students’ digital literacy - Lioni Anka Monalisa; Arika Indah Kristiana; Arif Fatahillah; Saddam Hussen; Laila Nurul Fatimah (JINoP (Jurnal Inovasi Pembelajaran), 2024)
Educational digitalization is characterized by technology-assisted media, leading to improved students’ digital literacy. One of these media is the electronic worksheet for students. An initial observation revealed that learning activities at Public Islamic Senior High School (MAN) in Bondowoso still operationalized conventional books as the sole media. This study aimed to develop electronic worksheets for students using valid, effective, and practical Geogebra-assisted live worksheets, guided by the 4-D model designed by Thiagarajan. This model consisted of four stages, i.e., define, design, develop, and disseminate. Data were collected through observation, tests, and questionnaires. Test questions were used to determine the level of effectiveness, and questionnaires were used for validity and practicality tests. The results revealed very high validity. The effectiveness analysis exhibited an N-Gain percentage of 76%, signifying a satisfactory effectiveness rate. The practicality analysis marked 86.20%, which is classified into a good category. The analysis results corroborated that electronic worksheets for students have proven valid, effective, and practical, demonstrating the potential to improve students' digital literacy.